Randomised controlled trial comparing intraoperative cell salvage and autotransfusion with standard care in the treatment of hip fractures: a protocol for the WHITE 9 study - Dickenson, E; Griffin, XL; Achten, J; Mironov, K; O'Connor, H; Parsons, N; Murphy, M; Wyse, M; Mason, J; Appelbe, D; Athwal, A; Griffin, D (BMJ Publishing Group, 2022)
Introduction People who sustain a hip fracture are typically elderly, frail and require urgent surgery. Hip fracture and the urgent surgery is associated with acute blood loss, compounding patients’ pre-existing comorbidities including anaemia. Approximately 30% of patients require a donor blood transfusion in the perioperative period. Donor blood transfusions are associated with increased rates of infections, allergic reactions and longer lengths of stay. Furthermore, there is a substantial cost associated with the use of donor blood. Cell salvage and autotransfusion is a technique that recovers, washes and transfuses blood lost during surgery back to the patient. The objective of this study is to determine the clinical and cost effectiveness of intraoperative cell salvage, compared with standard care, in improving health related quality-of-life of patients undergoing hip fracture surgery. Methods and analysis Multicentre, parallel group, two-arm, randomised controlled trial. Patients aged 60 years and older with a hip fracture treated with surgery are eligible. Participants will be randomly allocated on a 1:1 basis to either undergo cell salvage and autotransfusion or they will follow the standard care pathway. Otherwise, all care will be in accordance with the National Institute for Health and Care Excellence guidance. A minimum of 1128 patients will be recruited to obtain 90% power to detect a 0.075-point difference in the primary endpoint: EuroQol-5D-5L HRQoL at 4 months post injury. Secondary outcomes will include complications, postoperative delirium, residential status, mobility, allogenic blood use, mortality and resource use. Ethics and dissemination NHS ethical approval was provided on 14 August 2019 (19/WA/0197) and the trial registered (ISRCTN15945622). After the conclusion of this trial, a manuscript will be prepared for peer-review publication. Results will be disseminated in lay form to participants and the public. Trial registration number ISRCTN15945622.